Development of Piano Accompaniment Education in Chinese Art Songs, China - Ning, Tang; Pattananon, Nicha; Yukolthonwong, Supot (Journal of Modern Learning Development, 2023)
The development of piano accompaniment is becoming more and more mature with the evolution of art songs. Piano accompaniment plays an important role in the creation of art songs. Art songs without piano accompaniment will be incomplete. In addition to the interpretation and expression of art songs in the vocal part, piano accompaniment also bears important functions such as assistance, rendering, and supplementing, proving that the existence of piano accompaniment is an indispensable part of art songs. When interpreting art songs, piano accompaniment should have solid piano performance technology, a rich theoretical foundation, and stage performance experience, and also pay attention to the emotional expression of piano accompaniment in art songs. This is the sublimation of piano accompaniment and the real significance of piano accompaniment in art songs. The piano accompaniment of Chinese art songs has developed from school songs in the early 20th century to today's music form with its style characteristics.